Anterior horn atrophy in the cervical spinal cord: A new biomarker in progressive multiple sclerosis. (May 2023) - Tsagkas, Charidimos; Huck-Horvath, Antal; Cagol, Alessandro; Haas, Tanja; Barakovic, Muhamed; Amann, Michael; Ruberte, Esther; Melie-Garcia, Lester; Weigel, Matthias; Pezold, Simon; Schlaeger, Regina; Kuhle, Jens; et al.
Background: Spinal cord (SC) gray and white matter pathology plays a central role in multiple sclerosis (MS). Objective: We aimed to investigate the extent, pattern, and clinical relevance of SC gray and white matter atrophy in vivo. Methods: 39 relapsing–remitting patients (RRMS), 40 progressive MS patients (PMS), and 24 healthy controls (HC) were imaged at 3T using the averaged magnetization inversion recovery acquisitions sequence. Total and lesional cervical gray and white matter, and posterior (SCPH) and anterior horn (SCAH) areas were automatically quantified. Clinical assessment included the expanded disability status scale, timed 25-foot walk test, nine-hole peg test, and the 12-item MS walking scale. Results: PMS patients had significantly reduced cervical SCAH — but not SCPH — areas compared with HC and RRMS (both p  < 0.001). In RRMS and PMS, the cervical SCAH areas increased significantly less in the region of cervical SC enlargement compared with HC (all p  < 0.001). This reduction was more pronounced in PMS compared with RRMS (both p  < 0.001). In PMS, a lower cervical SCAH area was the most important magnetic resonance imaging (MRI)-variable for higher disability scores. Conclusion: MS patients show clinically relevant cervical SCAH atrophy, which is more pronounced in PMS and at the level of cervical SC enlargement.